ASSESSMENT OF ADRENOCORTICAL DYSFUNCTION IN PATIENTS WITH STABLE LIVER CIRRHOSIS - Chiriac, Ş. (Acta Endocrinol (Buchar), 2016)
INTRODUCTION: Relative adrenal insufficiency (RAI) is common in the setting of critical illness as well as in hemodynamically instable cirrhotic patients with sepsis. Several studies have also shown that RAI is frequent in patients with stable cirrhosis without sepsis. The aim of this study was to prospectively assess the incidence of RAI in patients with stable cirrhosis. PATIENTS AND METHODS: Forty-seven patients with hemodynamically stable liver cirrhosis without sepsis were prospectively included. RAI, assessed by using low dose-short Synacthen test (LD-SST), was defined as either a basal total cortisol concentration below 3.6 µg/dL or a peak total serum cortisol ≤ 16 µg/dL at 30 min after stimulation. RESULTS: RAI was present in 10 (21.3%) of 47 cirrhotic patients. Peak cortisol level was negatively correlated with the severity of cirrhosis evaluated by Child-Turcotte-Pugh (CTP) (r=-0.46; P=0.001) and Model for End-Stage Liver Disease (MELD) (r=-0.51; P=0.001) scores. The frequency of RAI increased from CTP-A (10%) to CTP-B (30%) to CTP-C (60%). CONCLUSION: RAI diagnosed by LD-SST is frequent in patients with stable cirrhosis and is related to the severity of liver disease. Further studies are needed to define clinical importance of RAI in stable cirrhotic patients.